PH-dependent syntheses, structural and spectroscopic characterization, and chemical transformations of aqueous Co(II)-Quinate complexes: An effort to delve into the structural speciation of the binary Co(II)-Quinic acid system - Menelaou, Melita; Konstantopai, A.; Mateescu, Constantin; Zhao, Hong; Lalioti, Nikolia; Salifoglou, Athanasios; Drouza, Chryssoula (My University, 2009)
Cobalt(II) is an essential metal ion, which can react with biologically relevant substrates in aqueous media, affording discrete soluble forms. D-( - )-quinic acid is a representative metal ion binder, capable of promoting reactions with Co(II) under pH-specific conditions, leading to the isolation of the new species K[Co(C 7H 11O 6) 3]·3CH 3CH 2OH (1), Na[Co(C 7H 11O 6) 3]·3CH 3CH 2OH·2.25H 2O (2), and [Co(C 7H 11O 6) 2(H 2O) 2]·3H 2O (3). Compounds 1 - 3 were characterized by elemental analysis, spectroscopic techniques (Fourier-transform infrared, UV - visible, electron paramagnetic resonance (EPR), electrospray ionization mass spectrometry), magnetic studies, and X-ray crystallography. Compound 1 crystallizes in the cubic space group P2 13, with a = 15.3148(19) Å, V = 3592.0(8) Å 3, and Z= 4. Compound 2 crystallizes in the orthorhombic space group P2 12 12 1, with a = 14.9414(8) Å, b= 15.9918(9) Å, c= 16.0381(9) Å, V= 3832.1(4) Å 3, and Z= 4. Compound 3 crystallizes in the monoclinic space group P2 1/m, with a = 13.2198(10) Å, b=5.8004(6)Å, c=15.3470(12) Å, β = 108.430(7), V= 1116.45(17) Å 3, and Z= 4. The lattices in 1-3 reveal the presence of mononuclear Co(II) units bound exclusively to quinate (1 and 2) or quinate and water ligands (3), thus projecting the unique chemical reactivity in each investigated system and suggesting that 3 is an intermediate in the synthetic pathway leading to 1 and 2. The octahedral sites of Co(II) are occupied by oxygens, thereby reflecting the nature of interactions between the divalent metal ion and quinic acid. The magnetic and EPR data on 1 and 3 support the presence of a high-spin octahedral Co(II) in an oxygen environment, having a ground state with an effective spin of S= 1/2. The significance of 3 is further reflected into the aqueous speciation of the binary Co(II) - quinic acid system, in which 3 appears as a competent participant linked to the solid state species 1. The physicochemical profiles of 1 -3, in the solid state and in solution, earmark the importance of aqueous structural speciation, which projects chemical reactivity pathways in the binary Co(II) - quinate system, involving soluble Co(II) forms emerging through interactions with low molecular mass O-containing physiological substrates, such as quinic acid
Keywords: Chemical structure; Chemistry; Infrared spectroscopy; Magnetism; Methodology; Temperature; X-ray crystallography